2018
DOI: 10.56093/ijas.v88i8.82573
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid linear time series approach for long term forecasting of crop yield

Abstract: Long term forecasting of crop production is required to establish long term vision, say by 2025, to meet growing demand of population at that point of time. Existing univariate linear time series ARIMA approach is valid for short term forecast only. In this paper, a technique for long term yield forecast has been proposed. Initially, we have tried to improve short term forecast of yield by using hybrid ARIMA through ANN approach. The forecast values of yield through hybrid approach was considered as baseline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The results of the DM test revealed that in two sets (training and testing set) of data, the extreme learning machine intervention model performed better than all other models (Table 8). According to several studies [38][39][40][41][42][43][44] for forecasting time series data in the agricul-tural and related fields, the results showed that AI performed better than the standard ARIMA model, which is in accordance with some previous findings. By considering the MAPE values, a significant difference between the actual and forecasted values can be obtained by the DM test.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the DM test revealed that in two sets (training and testing set) of data, the extreme learning machine intervention model performed better than all other models (Table 8). According to several studies [38][39][40][41][42][43][44] for forecasting time series data in the agricul-tural and related fields, the results showed that AI performed better than the standard ARIMA model, which is in accordance with some previous findings. By considering the MAPE values, a significant difference between the actual and forecasted values can be obtained by the DM test.…”
Section: Discussionsupporting
confidence: 87%
“…In order to address this issue, the ANN model was employed to capture the non-linear patterns present in the residuals. The ANN model was configured with appropriate lag lengths for both the input and hidden nodes (Alam et al, 2018). The findings revealed that 6-11-1 and 10-1-1 were the best networks fitted for the arrivals, while the 7-4-1 and 8-4-1 networks were fitted to the price series of Chandigarh and Delhi markets, respectively (Zhang, 2003).…”
Section: Arima-annmentioning
confidence: 99%
“…The networks fitted for the Chandigarh, Delhi, Dehradun and Shimla markets are 11-5-1, 9-9-1, 3-1-1 and 9-3-1. Chandigarh market consumed high (11) lags for the input node whereas the Delhi market consumed high (9) lags for the hidden node (Alam et al, 2018). The parameters of the fitted networks are 66, 100, 6 and 34 respectively.…”
Section: Ann Modelmentioning
confidence: 99%